Atherosclerotic Monstrous Double Aneurysm of the Left Main Coronary Artery: A Very Rare Angiographic Finding - Gerardo Musuraca; Ferdinando Imperadore; Clotilde Terraneo; Emiliano Boldi (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Coronary artery aneurysm is a rare disease diagnosed in 0.3 to 4.9% of patients undergoing coronary angiography. The incidence of left main coronary artery aneurysm (LMCAA) is extremely rare: 0.1% [1]. Coronary artery aneurysm involves the right coronary artery, the left anterior descending and circumflex coronary arteries in descending order of frequency [2] and atherosclerosis is the most common cause. Other causes include arteritis, Kawasaki disease, angioplasty sequelae, laser procedures, traumatic injury, dissection, connective tissue disorders, Takayasu's arteritis, congenital (anomaly or genetic disorders such as Ehler-Danlos syndrome, Marfan syndrome) mycotic and idiopathic diseases. Although surgery has been recommended to prevent complication, there are no large available data comparing medical and surgical therapy [3-5]. The LMCAA is a rare clinical entities, encountered incidentally in approximately 0.1% of patients undergone routine angiography [6,7]. The sizes of LMCAAs may be fusiform or saccular. Management of these cases is still controversial, based on anedoctal experience rather than controlled trials.